PERENCANAAN JARINGAN AIR BERSIH DI DUSUN DEMPEL DESA PLOSOGADEN KECAMATAN CANDIROTO KABUPATEN TEMANGGUNG - Retno Mayasari; Widiyanto Widiyanto; Azzah Balqis Sabbah; Isna Pratiwi (Litbang Pemas - Universitas Islam Lamongan, 2021)
Water is one of the basic human needs. The benefits of water resources include the provision of water for the needs of clean water, irrigation, agriculture, fisheries, etc. To know the availability of water and water needs and plan facilities that can meet these needs to know the amount, quality, provision time, location that requires water and water sources. Hamlet Dempel is located in the village of Plosogaden District Candiroto Temanggung district with a population of 770 (data 2003) with an area of 775 ha. Although the source of water comes from direct water sources the construction of clean water facilities in rural areas often experiences post-construction constraints and sustainability, thus the need to hold clean water network planning. The planning of this clean water network includes an analysis of the needs of clean water and planning a network of clean water piping gravity systems. The results of this study are; (1) The result of this analysis of clean water needs in the form of Proyeksi increase of ploso garden villagers, namely by geometric calculation model until 2030 is 2.773 people and Kneads clean water until 2030 based on the projected population of 2.773 is 1,2 liters / second.; (2) Planning the clean water piping network of this system by measuring the elevation of the spring with service area is 35,07 meters with the elevation of the spring area of 721,14 MDPL and the elevation of the service area of 686,07 MDPL so that the planning of clean water network system in Plosogaden village using gravity system, then broncaptering planning to meet the needs of clean water in Plosogaden village is 2x2x1.5 meters with a reinforced concrete structure. And reservoir planning to meet clean water needs in the village of Plosogaden is 3x3x2.5m with reinforced concrete structures.